2009 International Conference on eHealth, Telemedicine, and Social Medicine 2009
DOI: 10.1109/etelemed.2009.18
|View full text |Cite
|
Sign up to set email alerts
|

A New Telemedicine System for the Home Monitoring of Lung Function in Patients with Obstructive Respiratory Diseases

Abstract: The conventional pulmonary function tests are based on spirometry, which unfortunately doesn't produce accurate and reproducible results if performed without the supervision of specially trained staff. We recently showed that forced oscillation technique is best suited for the homemonitoring of respiratory patients. The aim of this study was to develop a real-time data processing algorithm for the automatic unsupervised assessment of the lung obstruction, a network architecture for the data transmission and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Modeling and experimental studies have suggested that low-frequency dependence of resistance reflects ventilation heterogeneity in the periphery of lung (10,13,28,30,39,42,47). We could not measure resistance below 5 Hz but we think it reasonable to assume that increased R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] reflects an increased heterogeneity, although we cannot state at which level of airway tree. Regions with different time constants as a result of micro-atelectases, hypoventilation, or nonuniform distribution of pleural pressure (3,4,9,19,20,22,33,38,41,54) are expected to produce parallel heterogeneities indeed, although also the interplay between increased chest wall and parenchymal stiffness and gas inertia in obesity can promote serial heterogeneities, as reported in animal models under different conditions (1,27).…”
Section: Comments On Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Modeling and experimental studies have suggested that low-frequency dependence of resistance reflects ventilation heterogeneity in the periphery of lung (10,13,28,30,39,42,47). We could not measure resistance below 5 Hz but we think it reasonable to assume that increased R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] reflects an increased heterogeneity, although we cannot state at which level of airway tree. Regions with different time constants as a result of micro-atelectases, hypoventilation, or nonuniform distribution of pleural pressure (3,4,9,19,20,22,33,38,41,54) are expected to produce parallel heterogeneities indeed, although also the interplay between increased chest wall and parenchymal stiffness and gas inertia in obesity can promote serial heterogeneities, as reported in animal models under different conditions (1,27).…”
Section: Comments On Methodologymentioning
confidence: 99%
“…Single-breath lung diffusion capacity for carbon monoxide (DL CO) was measured following the ATS/ERS recommendations (31). Predicted values were from Quanjer et al (43) for spirometry and lung volumes and from Cotes et al (7) for DL CO. Respiratory impedance was measured by a forced oscillation system previously described (8,14,15). Sinusoidal pressure oscillations (5, 11, and 19 Hz; ϳ2 cmH 2O amplitude) were generated by a 16-cm-diameter loudspeaker (model CW161N, Ciare, Italy) and applied at the mouth during tidal breathing.…”
Section: Lung Function Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…FOT measurements were cleaned automatically from artefacts using previously published filtering rules 29 and automatically sent to the study server. An algorithm generated respiratory alerts if a trend of worsening was detected in at least one of the following FOT parameters measured at 5Hz: inspiratory resistance (Rinsp), inspiratory reactance (Xinsp) or the difference between inspiratory and expiratory reactance (∆Xrs), an index of the presence of tidal expiratory flow limitation 30,31 .…”
Section: Protocolmentioning
confidence: 99%